2019
DOI: 10.1177/1087054719887789
|View full text |Cite
|
Sign up to set email alerts
|

Children With ADHD Engage in Less Physical Activity

Abstract: Background: Children with ADHD should engage in physical activity, given its known role as a treatment adjunct. Objective: The main objective of this study is to assess the relationship between ADHD diagnosis and physical activity among children in the United States. Methods: This retrospective population-based cross-sectional study used data from the 2016 caregiver reported, National Survey of Children’s Health (NSCH). Results: In the adjusted binary model, children with an ADHD diagnosis had 21% lower odds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…12 The putative associations of ASD, ADHD and being with excess weight are reasonable because, other than a disease, obesity and overweight are often used to describe excess adiposity and unhealthy eating patterns and lack of physical exercise are recognized as main drivers. 13 Individuals with ASD and ADHD showed less physical activity 14,15 and dysregulated diet composition, with atypical selectivity (e.g., prefer more calorically dense food). 16,17 Previous meta-analyses have linked obesity to ASD 18 and ADHD.…”
mentioning
confidence: 99%
“…12 The putative associations of ASD, ADHD and being with excess weight are reasonable because, other than a disease, obesity and overweight are often used to describe excess adiposity and unhealthy eating patterns and lack of physical exercise are recognized as main drivers. 13 Individuals with ASD and ADHD showed less physical activity 14,15 and dysregulated diet composition, with atypical selectivity (e.g., prefer more calorically dense food). 16,17 Previous meta-analyses have linked obesity to ASD 18 and ADHD.…”
mentioning
confidence: 99%
“…Hence, it may lead to overweight. 32,33 There were some limitations to the current study. First, there is a possibility of random errors due to self-reported questionnaire.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, our study showed that exercise improved the expression of BDNF in the DEHP-exposed rats, which may suggest a mechanism underlying the recovery of working memory in these rats. Exercise has been suggested as an effective adjunctive treatment for improving the symptoms of ADHD [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The neurophysiological changes induced by exercise, such as dopaminergic and noradrenergic systems, considerable overlap with the neuropathological mechanisms implicated in ADHD [36]. Exercise is suggested to be an effective adjunctive treatment for improving the symptoms of ADHD [37,38].…”
Section: Introductionmentioning
confidence: 99%